Development of E-Book Teaching Materials Using Kvisoft Flipbook Maker on Theme 9 Subtheme 1: Objects Around Us: Single and Mixed - Galuh Silvia; Windiyani, Tustiyana; Purnamasari, Ratih; Abdul Gani, Resyi (Journal of International Multidisciplinary Research, 2024)
This research aims to determine the feasibility and develop e-book teaching materials using kvisoft flipbook maker on the theme of 9 objects around us subtheme 1 single and mixed objects in class V of SDN Loji 2 Bogor City. The method used by Research and Development (R&D) is the ADDIE (Analyze, Design, Development, implementation, Evaluation) model, but this research is only up to implementation. They are producing e-book teaching materials using kvisoft flipbook maker with 19 student respondents. To test the feasibility, validation sheets of media experts, linguists, and material experts were used with results obtained in the suitable category for use in learning. The results of the research from the validator instruments of media experts, linguists, and material experts obtained an average of 92.45% and the results of the student response questionnaire obtained an average of 90.63%. Based on the results of research and development of e-book teaching materials using kvisoft flipbook maker, it can be categorized as suitable for use by students in the learning process.